Management of the pjok pkg program dissemination to improve teachers' pedagogical competence - Ferry Wibowo; Suharyanto H. Soro (At Turots: Jurnal Pendidikan Islam, 2025)
Physical Education, Sport, and Health (PJOK) plays a fundamental role in realizing the comprehensive development of students, encompassing physical, mental, social, and emotional domains. To enhance the quality of PJOK education, the PJOK Teacher Professional Development Program (PKG) was initiated as a strategic intervention to strengthen teacher competence, with a primary focus on pedagogical skills. This research comprehensively analyzes the dissemination management of the PJOK PKG Program and evaluates its impact on improving the pedagogical competence of PJOK teachers within the Bandung Regency and the Regional Branch Office of Education (KCD) Region VII West Java. Utilizing a qualitative case study approach, data were collected through in-depth interviews, direct participant observation, and rigorous document analysis involving PJOK teachers, school supervisors, and educational bureaucrats. The findings reveal that the dissemination management operates through four distinct phases: (1) highly structured and data-driven planning, (2) collaborative organization emphasizing distributed leadership, (3) participatory implementation utilizing blended learning and localized teacher working groups (KKG), and (4) continuous monitoring that directly translates into measurable pedagogical enhancements. The program significantly improved teachers' conceptual understanding of student-centered learning, their capacity to design innovative lessons, and their utilization of authentic assessments. Ultimately, effective dissemination management of the PKG PJOK serves as a vital catalyst for sustainable professional development, directly elevating the quality of physical education.